Kumpulan karangan C. Snouck Hurgronje - C. Snouck Hurgronje (INIS, 1992)
ast JIL. VII =C.1/ast jil.1 =c.1 jil.2 =c.1 jil.5 =c.1 jil.9 =c.1 jil.10 =c.1-2 jil.11 =c.1 jil.13 =c.1 jil.14 =c.1-2/ir,ji.10,c.3/tr, jil.3=c.1; jil.7=c.1; jil.1=c.2; jil.2=c.2; jil.3=c.2; jil.10=c.4; jil.14=c.3/en, jil.1=c.3